Paisajes, espacios y materialidades : arqueología rural altomedieval en la península ibérica - Prata, Sara,; Cuesta-Gómez, Fabián,; Tente, Catarina, 1972- (Access archaeology., 2022)
Rural landscapes are increasingly important when analysing the processes of change following the collapse of the Roman imperial structure. This volume presents contributions from key researchers in early medieval peasant archaeology in the north-western quadrant of the Peninsula, offering a multi-scale image of the main lines of ongoing research.